Human Person in the Code of Canon Law of John Paul II - Přibyl, Stanislav (Philosophy and Canon Law, 2021)
The Code of Canon Law, promulgated by John Paul II in 1983, is a synthesis of the earlier 1917 Code and the doctrine of the Second Vatican Council. The Code contains norms which go well beyond a reform of the inner legal relations within the Catholic Church. A lot of them deal with the value and dignity of the human person, which shows a clear impact of the pontificate of John Paul II, who put a lot of emphasis on the given issue. The article discusses the fields of legal regulations in the Code which touch upon the issue of the human person, esp. freedom of religion, protection of unborn life, social rights, legal standing of women and the education of future generations. It points out the main difference between civil law (which also serves the dignity of the human person) and canon law, namely, the latter aims at the salvation of souls.